Hubungan Pengetahuan Dan Pola Makan Dengan Kejadian Tonsilitis Pada Anak Di Puskesmas Tehoru Tahun 2022 - Kayus Jamlean (Jurnal Ilmiah Kedokteran dan Kesehatan, 2022)
Inflammation of the tonsils, lay people often call tonsils. Everyone has tonsils, for some reason the tonsils can become inflamed which should not be underestimated. Tonsillitis is inflammation of the palatine tonsils which are part of the Waldeyer ring (Suroso, 2019). Tonsillitis is an infectious disease that occurs quite often, especially in children aged 5-15 years compared to adults (Koes Irianto, 2019). This study aims to determine the relationship between knowledge and eating patterns with the incidence of tonsillitis in children at the Tehoru Health Center, Central Maluku Regency. This research uses an observational research design with analytical survey research methods and uses a cross sectional study approach. The population in this study were Tonsillitis patients aged 6-15 years who received treatment at the Tehoru Health Center, Central Maluku Regency from January – June 2022, totaling 280 patients. Sampling using the Purposive Sampling technique obtained 31 respondents according to the inclusion criteria. Data were collected using questionnaires and observation sheets, the data collected was then processed and analyzed using the SPSS computer program. Data analysis includes univariate analysis by looking for frequency distributions and bivariate analysis with the chi-square test (a<0.05) to determine the relationship between variables. The results of the bivariate analysis showed a value of p=0.069 for the relationship between knowledge and the incidence of tonsillitis, and p=0.001 for the relationship between diet and the incidence of tonsillitis. So it can be concluded that there is no relationship between knowledge and the incidence of tonsillitis and there is a relationship between diet and the incidence of tonsillitis in children at the Tehoru Community Health Center, Central Maluku Regency in 2022.